SYSTEM FOR PRODUCING ENERGY FUEL FROM BIOMASS (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2024)
The paper presents a functional and structural analysis of the energy fuel production system from straw. The basic technology of processing straw as a component of compound feed for feed purposes has been identified. An energy-saving technology with combined processes of grinding and drying straw pulp for the production of pellets for energy purposes is proposed. The use of a solar collector for heating air and solar panels for generating electric energy in the daytime allows you to replace energy consumption during the processing of straw into energy pellets by up to 60%. The efficiency of drying and grinding processes increases, which leads to the creation of a more sustainable and environmentally friendly production of energy fuel from straw raw materials with zero cost.
Keywords: crushing and drying plant; solar collector; solar panel; energy fuel; pellets